Free Segmental Vastus Lateralis Muscle Flap for Reconstruction of Recalcitrant Defects of the Cleft Hard Palate - Acartürk, Tahsin Oğuz (Journal of Reconstructive Microsurgery, 2012)
Introduction Large recalcitrant defects of the anterior palate due to clefting are difficult to close with local tissues. In some cases distant tissue transfer may be the only option. Free segmental vastus lateralis muscle with its long high-caliber pedicle and low donor-site morbidity may be a good option.Patient/Method An 8-year-old girl with bilateral cleft lip and palate was evaluated for a defect in the anterior hard palate. She had four failed palate closures resulting in a 3.2 × 2.8 cm defect with severely scarred surrounding palatal tissues and severely hypernasal speech. A vastus lateralis muscle with a 7-cm pedicle was prepared. Only a 5 × 4 × 1 cm segment of muscle was harvested based on segmental motor innervations, thus sparing 90% of the remaining muscle. Vessels were anastomosed to the facial artery and vein through a facial tunnel. The flap was directed into the palatal defect via the right alveolar cleft and sutured in a fashion to prevent dehiscence and fistulization.Results The surface of the flap mucosalized over an 8-week period. The defect was completely closed. The speech markedly improved. There was no donor-site morbidity.Conclusion Free segmental vastus lateralis muscle offers easy harvest, a two-team approach, long pedicle length, a highly vascularized flap, and no functional loss.
Keywords: cleft palate; vastus lateralis muscle flap; hard palate reconstruction